Meeting Report: Consensus Recommendations for a Research Agenda in Exercise in Solid Organ Transplantation. Issue 10 (18th August 2014) - Mathur, S.; Janaudis‐Ferreira, T.; Wickerson, L.; Singer, L. G.; Patcai, J.; Rozenberg, D.; Blydt‐Hansen, T.; Hartmann, E. L.; Haykowsky, M.; Helm, D.; High, K.; Howes, N.; et al.
<x xml:space="preserve">Abstract</x> With improved survival rates in solid organ transplantation there has been an increased focus on long‐term outcomes following transplant, including physical function, health‐related quality‐of‐life and cardiovascular mortality. Exercise training has the potential to affect these outcomes, however, research on the optimal timing, type, dose of exercise, mode of delivery and relevant outcomes is limited. This article provides a summary of a 2‐day meeting held in April 2013 (Toronto, Canada) in which a multi‐disciplinary group of clinicians, researchers, administrators and patient representatives engaged in knowledge exchange and discussion of key issues in exercise in solid organ transplant (SOT). The outcomes from the meeting were the development of top research priorities and a research agenda for exercise in SOT, which included the need for larger scale, multi‐center intervention studies, development of standardized outcomes for physical function and surrogate measures for clinical trials, examining novel modes of exercise delivery and novel outcomes from exercise training studies such as immunity, infection, cognition and economic outcomes. The development and dissemination of "expert consensus guidelines, " synthesizing both the best available evidence and expert opinion was prioritized as a key step toward improving program delivery.